EMI FOR ENGINEERING-TECHNOLOGY STUDENTS IN VIETNAM: CHALLENGES & SUGGESTIONS - Dong, Lam Quang; Le, Phan Thi Ngoc; Tuyet, Nguyen Thi (VNU Journal of Foreign Studies; Vol 38 No 5DO - 10.25073/2525-2445/vnufs.4869, 2022)
The paper aims to shed light on EMI challenges from the perspective of engineering-technology students at various universities in Vietnam where EMI is in current and popular usage. A total of 307 questionnaires were delivered and returned, among which 288 were qualified, and 27 respondents were selected for in-depth interviews. Data from the questionnaires and interviews were analyzed along with information gathered from respondents’ journals. The findings indicate that Vietnamese engineering-technology students encountered different EMI-related challenges, typically subject matter content and vocabulary. They suggest several solutions, such as teachers using both Vietnamese and English rather than solely English in EMI classes. It is hoped that learners' perceptions of the difficulties they encountered and their proposed solutions to cope with such difficulties will help relevant stakeholders to make appropriate adjustments to the teaching methods and content accordingly, which is the key message that this study yields.